TEACHER COMPETENCY DEVELOPMENT WITH CSCT MODEL AND PISA FRAMEWORK INTEGRATION - Linda Sutanto; Badri Munir Sukoco; Sri Pantja Madyawati; Erick Fajar Subhekti (Universitas Airlangga, 2025)
The Noble Teacher Program enhances teacher competency in Indonesia through the CSCT Model and PISA Framework. It addresses training gaps by creating a sustainable framework aligned with global standards. The program began with Focus Group Discussions (FGDs) involving 20 education experts to identify needs and design a training model. Subsequently, 50 high school teachers in Surabaya participated in workshops and mentoring to improve pedagogical skills, critical thinking, social-emotional competencies, and technology integration. Evaluations showed significant improvements in teacher skills. Formative assessments identified program strengths and improvement areas, while pre-test and post-test comparisons confirmed gains in pedagogical and technological competencies, positively impacting classroom practices. The study concludes that the Noble Teacher Program effectively leverages community engagement to enhance education quality, aligning teacher competencies with global benchmarks. It provides a replicable model for integrating sustainability and global standards into teacher training initiatives.